2012
DOI: 10.1016/j.stem.2012.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Activates an Atypical PKC-CBP Pathway to Promote Neurogenesis and Enhance Spatial Memory Formation

Abstract: Although endogenous recruitment of adult neural stem cells has been proposed as a therapeutic strategy, clinical approaches for achieving this are lacking. Here, we show that metformin, a widely used drug, promotes neurogenesis and enhances spatial memory formation. Specifically, we show that an atypical PKC-CBP pathway is essential for the normal genesis of neurons from neural precursors and that metformin activates this pathway to promote rodent and human neurogenesis in culture. Metformin also enhances neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
299
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(327 citation statements)
references
References 28 publications
15
299
2
4
Order By: Relevance
“…Several studies have shown that metformin is effective in reducing ischemic injury 12. The mechanisms underlying this protection include the following: inflammation inhibition,14 blood‐brain barrier protection,13 promotion of neurogenesis and enhancement of spatial memory formation,38 promotion of the growth of nerve and recovery,39, 40 and improvement of poststroke angiogenesis and recovery 40. Consistent with previous studies, herein, our data demonstrate that long‐term metformin pretreatment affords strong neuroprotection and can be lifesaving under the conditions of CA/CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that metformin is effective in reducing ischemic injury 12. The mechanisms underlying this protection include the following: inflammation inhibition,14 blood‐brain barrier protection,13 promotion of neurogenesis and enhancement of spatial memory formation,38 promotion of the growth of nerve and recovery,39, 40 and improvement of poststroke angiogenesis and recovery 40. Consistent with previous studies, herein, our data demonstrate that long‐term metformin pretreatment affords strong neuroprotection and can be lifesaving under the conditions of CA/CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggesting a variety of benefi cial effects of metformin on aging ( 23 ), memory ( 112 ), and cardiovascular function ( 113 ) would argue that such trials should examine nononcologic health outcomes as well. However, many of the antineoplastic mechanisms of action of biguanides that operate in preclinical models may not be addressed in these trials, as drug accumulation in target tissues may not be suffi cient.…”
Section: Challenges For Future Researchmentioning
confidence: 99%
“…Therefore, metformin has been used for life extension in mammals and, in some studies although not all, has demonstrated gerosuppressive effects (Smith et al 2010;Anisimov et al 2011;Berstein 2012). Interestingly, 12 days of treatment with metformin has been shown to increase adult neurogenesis and spatial memory (Wang et al 2012). However, the effect of longer term treatment remains unknown.…”
Section: Introductionmentioning
confidence: 99%